A review of road infrastructure development and contemporary degradation on K'gari-Fraser Island. Issue 2 (3rd April 2021) - Waldron, Ross Pennycuick; McCallum, Adrian Bruce
ABSTRACT: Unpaved roads are often of poor quality in parks globally, particularly where funding and resources are limited. We review the history of road infrastructure development and provide contemporary evidence of road degradation on World Heritage listed K'gari-Fraser Island to demonstrate a need for a more sustainable transport system. Historical industry from mining and timber exploitation has established but also deeply impacted many sections of the island's roads. Contemporary observations reveal high volumes of vehicular traffic contributing to erosion and deep-cuttings on many sections of this international tourist destination that attracts approximately 450, 000 visitors per annum. Current observations of road degradation show that a more sustainable transport system should be implemented to mitigate further erosion from vehicular and weather impacts. The article provides justification for the need for sustainable transport solutions and strategies based on a history of inland sand road degradation and erosion leading to environmental impacts on K'gari-Fraser Island. Photographic evidence of varying degrees of degradation and erosion currently occurring and from past industry on K'gari's roads is provided in this article to strengthen the argument for a more sustainable transport network.